Exercise-induced rib stress fractures: potential risk factors related to thoracic muscle co-contraction and movement pattern - Vinther, A.; Kanstrup, I.-L.; Christiansen, E.; Alkjær, T.; Larsson, B.; Magnusson, S. P.; Ekdahl, C.; Aagaard, P. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The etiology of exercise-induced rib stress fractures (RSFs) in elite rowers is unclear. The purpose of the study was to investigate thoracic muscle activity, movement patterns and muscle strength in elite rowers. Electromyographic (EMG) and 2-D video analysis were performed during ergometer rowing, and isokinetic muscle strength was measured in seven national team rowers with a history of RSF and seven matched controls (C).